PENDUGAAN KEPEKAAN KAYU KARET TERHADAP SERANGAN KUMBANG AMBROSIA - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1988)
An  experiment   to  assess  the  susceptibility  of  rubber wood   (Hevea  brasiliensis)  to  ambrosia  beetle  infestations   was conducted   in a rural area,  near a rubber  plantation   in Jasinga,  Bogor. Fresh cut  rubber wood, each of  75 cm in length  1:1 and of  about  25  cm  in diameter, were prepared  for four  treating  conditions   including  freshly   cut, debarked,   and coated  with flint  kote,  and  (in a prepared  bore hole  made  on  the  middle  of  test  logs with  2.5 methanol   96%. The  extent  of the  beetle  infestations were  then  observed  and  recorded.The  test  results  revealed  that  the  degree of  rubber log susceptibility   to ambrosia  beetle  infestations   was affected   by the  treatments.  The  debarked   logs  were  highly   infested   by  the  beetles  in  less than  nine days  after  the  treatment   while the  un barked  ones  were still  soundly   left  in  the  field  for  more  than  one  month.   Significant   increase  in  log susceptibility due  to  the  treatments   with  ethanol   and  flint   kote  was also recorded  even  though  the  beetle  infestations   were not so high then  those  on  the  debarked  ones.